Amphicrine carcinoma of the stomach and intestine: a clinicopathologic and pan-cancer transcriptome analysis of a distinct entity - Huang, Dan (Cancer Cell Int, 2019)
BACKGROUND AND AIM: Amphicrine carcinoma, in which endocrine and epithelial cell constituents are present within the same cell, is very rare. This study characterized the clinicopathologic and survival analysis of this tumor, further compared the genetic diversities among amphicrine carcinoma and other tumors. MATERIALS AND METHODS: The clinicopathologic characteristics and survival outcomes of amphicrine carcinoma in this study were analyzed. The pan-cancer transcriptome assay was utilized to compare the genetic expression profile of this entity with that of conventional adenocarcinoma or neuroendocrine tumors. RESULTS: Ten cases (all in male patients) were identified in the stomach or intestine, with a median patient age of 62 years. There were characteristic patterns in the tumors: tubular, fusion or single-file growth of goblet- or signet ring-like cells. Four tumors were classified as low-grade and 6 as high-grade according to the histologic architecture. All cases were positive for neuroendocrine markers (synaptophysin and chromogranin A) and showed intracellular mucin in the amphicrine components. Four cases exhibited mRNA expression patterns showing transcriptional homogeneity with conventional adenocarcinomas and genetic diversity from neuroendocrine tumors. During the follow-up period, 3 patients died of disease, all of whom had high-grade tumors. Patients with high-grade amphicrine carcinoma had worse outcomes than those with low-grade tumors. CONCLUSIONS: This study confirms the morphological, immunostaining and transcriptome alterations in amphicrine carcinoma distinct from those in conventional adenocarcinomas and neuroendocrine tumors, but additional studies are warranted to determine the biological behavior and therapeutic response.